APPLICATION AND ANALYSIS OF GEOMETRIC DIMENSIONING AND TOLERANCING OF ASTRA MANUFACTURING POLYTECHNIC MINI CNC MILLING MACHINES CONSTRUCTION - Syaifullah, Herry
Astra Manufacturing Polytechnic or better known as Polman Astra since 2009 provides scholarships for outstanding students to cover 35% of the total number of students recruited from all over Indonesia. In addition to providing scholarships, as a form of implementation of tri-dharma perguruan tinggi (the threeresponsibilities